PWE-121 Faecal Calprotectin Levels of 50–200: Endoscopic Findings and Subsequent Diagnoses. (17th August 2016) - Sartain, S; Stone, A
Abstract : Introduction: Faecal calprotectin (FC) is a marker of intestinal inflammation, used to investigate gastrointestinal symptoms for inflammatory bowel disease (IBD). The normal range and significance of mild elevations in FC remains under debate. This study aimed to determine endoscopic findings and conditions associated with levels of 50–200. Methods: Data was collected retrospectively. Details of patients with FC of 50–200 received by St Richard's Hospital pathology department over an 11 month period were obtained. Results were reviewed with clinical information from clinic letters and investigations that were available 9 months after the FC collection period. Results: 189 patients had a FC of 50–200, with 109 having clinical information available. The remaining 80 not seen in secondary care were excluded. Of the 109 patients included, mean FC was 102.7, 73 were female and mean age 47.3 years. The most prevalent symptoms were abdominal pain (46.8%) and diarrhoea (64.2%). 82 (75.2%) patients underwent endoscopy, (54 colonoscopies, 32 flexi-sigmoidoscopies), with 10 procedures done before. 47 (57.3%) patients had normal endoscopies, with 34 (63%) colonoscopies being normal. Abnormalities included inflammation, ulcers, diverticulosis and polyps with low grade dysplasia. 51 patients had mucosal biopsies at recent endoscopy, with 12 showing inflammation. From these 12 patients; mean FC was 135.9, though 3 had FC < 100, 4 were diagnosed with IBD (mean FC = 167.5), 2 followed up for possible IBD, 1 had collagenous colitis, 3 had non-specific colitis and 2 had infective colitis. All patients with IBD or possible IBD had FC ≥ 100, with mean FC of 158.3. Patients with no inflammation on biopsy had mean FC of 100.3. Clinic letters showed 37 (33.9%) patients had a diagnosis of irritable bowel syndrome (IBS), with mean FC of 97. 21 (19.3%) patients with normal investigations lacked a formal diagnosis, being mostly discharged or not followed up. Many patients avoided endoscopy as alternative diagnoses were made. Other diagnoses included chronic pancreatitis (5.5%), gastroenteritis (5.5%), coeliac disease (2.8%), diverticulosis (5.5%) or symptoms improved (3.7%). Conclusion: FC levels of 50–200 have a low association with subsequent diagnosis of IBD (3.6%). Many patients were diagnosed with IBS or had normal investigations indicating a functional condition. In this range of FC, patients with inflammation on biopsy had a higher FC than those with negative biopsies (p < 0.05). Inflammation caused by IBD had a higher FC than other causes of inflammation. Negative predictive values of FC 50–99 were higher than FC 100–200 with regards to excluding IBD (100% v 91.8%) and mucosal inflammation if undergoing endoscopy (95% v 81.6%). Many patients with FC 50–200 were not referred to secondary care. This study suggests a low rate of missed IBD is likely as a result. Disclosure of Interest: None Declared